2015
DOI: 10.1111/1467-856x.12073
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Voters Lose Trust in Governments? Public Perceptions of Government Honesty and Trustworthiness in Britain 2000–2013

Abstract: This article:• Notes that public perceptions that governments are honest and trustworthy are surprisingly volatile over time, but they move together in a long-term equilibrium relationship with indicators of policy performance and perceptions of fairness of the decision-making process.• Argues that if individuals feel that policy delivery, particularly in relation to the economy, is working well then they will trust the government of the day even if they oppose a particular decision.• Maintains that if they fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 57 publications
2
42
0
6
Order By: Relevance
“…In England, there is a growing political divide between cosmopolitan areas of economic growth and backwaters of decline, but what unites them is a dislike of politicians . In the United Kingdom, several crises have helped to erode public trust in government, including the Iraq War, the MPs' expenses scandal, and recent austerity measures (Koch 2016;Whiteley et al 2015). The alienation from politics, or anti-politics, is often classified as either a demand side or a supply side problem.…”
Section: Risk Society De-politicisation Post-politics and Anti-polmentioning
confidence: 99%
See 1 more Smart Citation
“…In England, there is a growing political divide between cosmopolitan areas of economic growth and backwaters of decline, but what unites them is a dislike of politicians . In the United Kingdom, several crises have helped to erode public trust in government, including the Iraq War, the MPs' expenses scandal, and recent austerity measures (Koch 2016;Whiteley et al 2015). The alienation from politics, or anti-politics, is often classified as either a demand side or a supply side problem.…”
Section: Risk Society De-politicisation Post-politics and Anti-polmentioning
confidence: 99%
“…There are also issues of social justice with regards to fracking. The "desolate" north has been identified as more suitable for fracking and, due to its industrial heritage, likely to be more accepting of the process (Cotton 2017;Webb 2013). Fracking remains contested, and the government in May 2018 suggested that the exploratory process should become part of Permitted Development and the Nationally Significant Infrastructure Projects regime (Clark 2018;Ward 2018).…”
mentioning
confidence: 99%
“…In England there is a growing political divide between cosmopolitan areas of economic growth and backwaters of decline but what unites them is a dislike of politicians (Jennings and Stoker 2016). In the UK, several crises have helped to erode public trust in government, including the Iraq War, the MPs expenses scandal and recent austerity measures (Koch 2016, Whiteley et al 2015. The alienation from politics or anti-politics is often classified as either a demand side or a supply side problem.…”
Section: Risk Society De-politicisation and Anti-politicsmentioning
confidence: 99%
“…This trend is not unique to Australia, of course. Trust levels are falling internationally [18], [24], however, there have been significant evolutions and variations to traditional Australian democracy therefore. These include government reform agendas, policy developments that place community trust at the centre of implementation [11], the government commission of new communication technologies and blossoming entrepreneurial endeavours into new forms of democracy.…”
Section: Introductionmentioning
confidence: 99%